Intelligent design and visual simulation of human product interactions in a virtual environment - Lim, Samuel Yoke Eng (2008)
This project addresses this issue from a multi-disciplinary approach that optimises theapplications of ergonomics, visual simulation, knowledge-based systems and intelligentnetworks for the analysis and optimisation of the complex relationships between theproduct and its intended users. It developed a suite of modules that possesses appropriateintelligence, while at the same time allows the users to interact with the design or productintuitively in a virtual environment. The characteristics of both the end-users (the onesoperating and navigating in the virtual environment) and the designers/trainers (thosedesigning and/or specifying suitable environment and training scheme to the end-users)were considered. With the knowledge of experts acquired and built into the intelligentmodule, the system can assume the routine tasks of the designers/trainers withoutcompromising it efficacy.